2020
DOI: 10.3390/mi11050484
|View full text |Cite
|
Sign up to set email alerts
|

A Review of MEMS Capacitive Microphones

Abstract: This review collates around 100 papers that developed micro-electro-mechanical system (MEMS) capacitive microphones. As far as we know, this is the first comprehensive archive from academia on this versatile device from 1989 to 2019. These works are tabulated in term of intended application, fabrication method, material, dimension, and performances. This is followed by discussions on diaphragm, backplate and chamber, and performance parameters. This review is beneficial for those who are interested with the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 126 publications
(138 reference statements)
0
60
0
Order By: Relevance
“…Silicon-microfabricated free-standing membranes have been developed for several applications ranging from pressure sensors [10] to microphones [11] and microheaters [12]. Among the commercially available microfabricated membranes, some different options are available.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon-microfabricated free-standing membranes have been developed for several applications ranging from pressure sensors [10] to microphones [11] and microheaters [12]. Among the commercially available microfabricated membranes, some different options are available.…”
Section: Introductionmentioning
confidence: 99%
“…Microphones are used in a wide array of consumer products, such as smart phones, smart watches, laptops, headsets, and tablets [1]. Today, the most widely used type of microphone is the Micro Electro-Mechanical System (MEMS) microphone, as this type of microphone may have a long range of benefits over the alternatives [2].…”
Section: Introductionmentioning
confidence: 99%
“…The dominant contribution to noise in MEMS microphones is the squeezed-film effect [1], [4], which can be reduced by increasing the distance between the backplate and the diaphragm of the microphone. However, doing this will also reduce the signal strength, unless the bias voltage is increased as the air gap is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the freestanding 3C-SiC cantilever, the use of a 3C-SiC diaphragm in MEMS sensors is equally important, especially for applications in extreme environments [1,4]. In terms of its use as an acoustic sensor, we performed a comprehensive literature review on the articles that published prototypes of MEMS microphones in the past 30 years [22]. We found that silicon carbide has never been employed as the acoustic diaphragm.…”
Section: Introductionmentioning
confidence: 99%